Peran Dewan Pengawas Syariah Dalam Penerapan Good Corporate Governance Dalam Pencegahan Fraund Financing di Bank Syariah - Analia, Fitra; Abdullah, Muhammad Wahyuddin; Muchlis, Saiful (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The act of misrepresentation in a monetary establishment is something that can be a significant danger to the maintainability of an organization's business. As a result, it is critical that efforts to prevent fraud are made to lessen the impact on stakeholders and customers. One way to do this is by putting good corporate governance into place. This study aims to determine how the presence of a sharia-compliant supervisory board in an Islamic bank, one form of good corporate governance, reduces the financing of fraudulent activities. The method of conducting the literature review and the qualitative research approach were utilized, and secondary data were used as the type of data. The findings of this study indicate that an Islamic bank's maximum application of good corporate governance is thought to be capable of preventing the practice of fraud financing. This is especially true when the Islamic supervisory board is maximized in supervising the implemented operations that have met the sharia compliance aspect. The presence of a sharia supervisory board is not only a distinguishing feature between Islamic banks and conventional banks; it is also a representation of the implementation of GCG. If the existence of a sharia Keywords : sharia supervisory board, good corporate governance, fraund financing.